Design of a vineyard terrestrial robot for multiple applications as part of the innovation of process and product : preliminary results - López Castro, Andrea; Marroquin Jacobo, Angie; Soto Amador, Ana; Padilla Davila, Elias; López-Leyva, Josué Aarón (My University, 2020)
This paper presents the customized design of a terrestrial robot for applications in vineyards, although it focuses more on the process of applying micronutrients to grapes. The detailed design of the parts and the complete modeling of all the devices and wiring are shown based on the needs and challenges of the mentioned applications, such as the difficulty of moving in different terrains types, humidity, among other variables. The digital prototype also considers the use of various types of cameras to determine plant health and monitor the actual path in the vineyards. As final results, the designs and technological proposals are shown, as well as the summarized of the innovation of process and product based on the technical feedback of companies (Early-Adopters) that evaluated the project.
Indexación Scopus
Keywords: Wiring; Tecnological innovation; Robot vision System; Prototypes; Cameras; Proposals; Campus Ensenada